Impact of γ-irradiation or heat pasteurisation treatment on nutritional and immunological properties of human milk. (December 2021) - Robichaud, Valerie; Aguilar-Uscanga, Blanca R.; Millette, Mathieu; Allahdad, Zahra; Lacroix, Monique
Abstract: The nutritional and microbiological quality of human milk (HM) before and after spray drying was compared. The results showed that the atomisation of untreated-HM did not significantly change protein, lactose and fat content. The immunoglobulins showed a retention from 70 to 82% for IgA, IgG and IgM. γ-Irradiation (3, 5 and 10 kGy) of frozen and powdered milk as well as Holder pasteurisation (HoP; 62.5 °C for 30 min) of liquid milk were used to decontaminate milk. A dose of 5 kGy irradiation resulted in 99.7% destruction of the total aerobic flora in the powdered milk and in the frozen milk, while it was 95.1% for HoP-treated milk. Macronutrients and bioactive compounds (lysozyme and amylase) present in atomised HM were not affected by γ-irradiation even at a dose of 10 kGy. Despite a slight increase in malondialdehyde, treatment with irradiation at 10 kGy did not alter the antioxidant potential.